Study of Hydride Formation in Metallic Systems - C. S. Pande; M. A. Imam; D. J. Singh; R. L. Holtz; D. A. Meyn (The Minerals, Metals and Materials Society, 1994)
"Various theoretical and experimental techniques used to search and develop new metal hydride systems suitable for hydrogen storage are described. The main theoretical technique under study makes the use of electronic structure of the candidate materials. Microstructural characterization techniques like transmission electron microscopy are being used to study the hydride formation. Novel processing techniques for material preparation such as those needed to produce thin films or amorphous phases are also being utilized. The techniques are illustrated with results from Pd, FeTi and Mg2Ni systems.IntroductionOf the four methods of hydrogen storage, compressed gas, cryogenic liquid, metal hydrides, and gas-solid adsorption, the metal hydride storage method is more attractive from the point of view of high volumetric density and safety. Compressed gas storage has disadvantages of extreme pressure, weight, and volume requirements, whereas storage of hydrogen as cryogenic liquid is unattractive due to the requirements of extremely low temperatures and high consumption of primary energy. Moreover, the number hydrogen atoms present in a volume of 10- 22 Cm3 (nH) in liquid hydrogen state (- 20K) is 4.2 whereas number of hydrogen atoms that can be accommodated in a free volume of 10-22 cm3 of various hydrides are as follows: LiH--5.9, TiH2--9.2, ZrH2--9.2, VH2--l0.2. High hydrogen concentration is usually associated with a large H/Metal atomic ratio but is also a function of structure."